Exercise and large airway issues - Zander J. Williams; Giovanni Cenerini; James H. Hull (Physiological Reports)
Abstract The large airways, extending from the trachea to the main bronchi, respond dynamically to exercise‐induced ventilatory demands. Large airway collapse (LAC) represents a spectrum of conditions characterized by excessive reduction in tracheal and/or main bronchial lumen during expiration. Utilizing the most common diagnostic criteria, defined as ≥50% reduction in airway cross‐sectional area during expiration, LAC is a common finding in around one in three patients with underlying lung disease. However, it is also apparent that healthy, asymptomatic people meet this diagnostic criteria. Despite being recognized as a cause of exertional symptoms, the relationship between LAC and exercise‐related symptoms or limitation is currently poorly understood. Traditional clinical approaches use forced expiratory measurements performed at rest during bronchoscopy or imaging studies to assess the condition. But novel tests, visualizing the large airways during exercise, may provide more physiologically relevant insight and are an important next step towards the development of targeted interventions for this clinical entity. This review aims to examine large airway behavior during different ventilatory challenges, with particular focus on comparing exercise hyperpnea with forced expiratory maneuvers.